Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1126/science.1253320
|View full text |Cite
|
Sign up to set email alerts
|

Niche engineering demonstrates a latent capacity for fungal-algal mutualism

Abstract: Mutualistic symbioses shape the evolution of species and ecosystems and catalyze the emergence of biological complexity, yet how such symbioses first form is unclear. We show that an obligate mutualism between the yeast Saccharomyces cerevisiae and the alga Chlamydomonas reinhardtii—two model eukaryotes with very different life histories—can arise spontaneously in an environment requiring reciprocal carbon and nitrogen exchange. This capacity for mutualism is phylogenetically broad, extending to other Chlamydo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
183
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(192 citation statements)
references
References 66 publications
8
183
0
1
Order By: Relevance
“…Overall, these data demonstrate that the external supply of NH 4 + breaks the reciprocal dependency of this syntrophy and allows E. coli to rapidly overtake the coculture due to its lower intrinsic generation time relative to that of R. palustris (2.5 h versus 9.9 h), and ultimately prevent R. palustris growth. These results, in combination with the acetate results discussed above, also corroborate the notion that stable coexistence relies on the metabolic dependence of the faster-growing species on its slower-growing partner and not the converse (Hom and Murray, 2014).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Overall, these data demonstrate that the external supply of NH 4 + breaks the reciprocal dependency of this syntrophy and allows E. coli to rapidly overtake the coculture due to its lower intrinsic generation time relative to that of R. palustris (2.5 h versus 9.9 h), and ultimately prevent R. palustris growth. These results, in combination with the acetate results discussed above, also corroborate the notion that stable coexistence relies on the metabolic dependence of the faster-growing species on its slower-growing partner and not the converse (Hom and Murray, 2014).…”
Section: Resultssupporting
confidence: 78%
“…High cross-feeding levels can be detrimental to a mutualism Cross-feeding levels are inherently difficult to measure and yet are hypothesized to be a major determinant of mutualism dynamics and stability (Shou et al, 2007;Kim et al, 2008;Estrela et al, 2012;Hom and Murray, 2014). We therefore used our model to address the effect of NH 4 + -cross-feeding levels on mutualism dynamics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, the majority of studies of microbial mutualisms have focused on cross-feeding, the mutually beneficial exchange of metabolites (10)(11)(12)(13)(14)(15)). Studies involving cross-feeding amino acid auxotrophs (10)(11)(12) found that the division of labor within the mutualism can increase the fitness of cross-feeding cocultures compared with a self-sufficient strain (10).…”
mentioning
confidence: 99%